Partial empty Sella syndrome in women-the significance of obstetric and lactational history - Agrohi, Jhalak; Kohli, Saksham; G. K., Adarsha; Sehdev, Ritvik; Agrohi, Daksh (International Journal of Research in Medical Sciences, 2023)
Empty Sella syndrome is an uncommon condition characterized by the shrinking or flattening of the pituitary gland, resulting in the filling of the Sella turcica with cerebrospinal fluid rather than the normal pituitary gland. In this report, we present a case of undiagnosed partial empty Sella syndrome, which was found to be caused by pituitary hypophysitis with an idiopathic etiology. The patient, a middle-aged individual, presented atypically with acute adrenal insufficiency induced by a lower respiratory tract infection. The diagnosis was made following an investigative work-up that took into consideration the presence of hypotension, electrolyte imbalances, and a history of two post-partum lactational failures. Hormonal supplements were used to manage the patient conservatively, and no significant complications were observed.